Skipping on the Grains of Multiverses Towards a Portal: World-Building Experience - Golovátina-Mora, Polina (Imaginations)

(untitled) (York University, 2021)
This essay is a fictional autoethnographic sensemaking of the experience during the long lockdown caused by the COVID-19 pandemic. The sensemaking mainly draws on the thought of Deleuze and Guattari and Karen Barad, with a methodology inspired by Donna Haraway’s conceptualisation of speculative fabulation. The experience is defined as multispecies migration in the multiverse. The essay is an exploration of relations between different forms of memories and associations that they produce in their interaction under the conditions of the current pandemic, as well as between the agencies involved and created in these relations. This includes childhood memories, immediate memories, readings, conversations, imaginative work, dreams, and cinematic images that form the worldview of the author. The essay experiments with the forms of exploration and its presentation to emphasize the intra-action between the content and the form of writing. The author aims to contest the linear idea of research and writing and expand the acceptable referential framework.